2015
DOI: 10.1002/0471142905.hg1114s84
|View full text |Cite
|
Sign up to set email alerts
|

Stranded Whole Transcriptome RNA‐Seq for All RNA Types

Abstract: Stranded whole transcriptome RNA-Seq described in this unit captures quantitative expression data for all types of RNA including, but not limited to miRNA (microRNA), piRNA (Piwi-interacting RNA), snoRNA (small nucleolar RNA), lincRNA (large non-coding intergenic RNA), SRP RNA (signal recognition particle RNA), tRNA (transfer RNA), mtRNA (mitochondrial RNA) and mRNA (messenger RNA). The size and nature of these types of RNA are irrelevant to the approach described here. Barcoded libraries for multiplexing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The estimate variation within each group were similar therefore student’s t -test was used to statistically analyze the significant difference among different groups by using Prism 4.0 (GraphPad Software). The genome-wide analysis experiments were conducted as described previously[ 56 , 57 ] using the Partek Genomics Suite (version 6.5).…”
Section: Methodsmentioning
confidence: 99%
“…The estimate variation within each group were similar therefore student’s t -test was used to statistically analyze the significant difference among different groups by using Prism 4.0 (GraphPad Software). The genome-wide analysis experiments were conducted as described previously[ 56 , 57 ] using the Partek Genomics Suite (version 6.5).…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were extracted, flash frozen and stored at 2808C. Subsequent generation of RNA libraries was carried out at the Center for Genomics and Bioinformatics at Indiana University following established protocols [14]. For additional information on RNA extraction and RNA libraries, see the electronic supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…Advances in high‐throughput deep sequencing of the transcriptome and the ENCODE project over the last two decades have demonstrated that only approximately 2% of the genome codes for proteins, while the largest genome fraction encodes for thousands of non‐coding RNAs . These results indicate that non‐coding RNAs, which were considered as “transcriptional noises,” play a critical role in the gene control across all kingdoms of life.…”
Section: Introductionmentioning
confidence: 99%